Antibacterial activity of two isolated endophytic extracts assosiated with Indonesian mangrove plant Rhizophora mucronata - Fareza, Muhamad Salman; Choironi, Nur Amalia; Harwoko, Harwoko; Sunarto, Sunarto (Pharmaciana, 2018)
Endophytic fungi are microorganisms reside in the living tissues of the host plant. This fungi can contribute to provide protection to the host from the infection caused by another microorganism. The one reasonable strategy to discover a new antibacterial agent from endophytic fungi are from the plant which lived in special condition such Rhizophora mucronata. The aim of this research is to determine antibacterial activity of the endophytic fungi extracts assosiated with Rhizophora mucronata from Sagara anakan. The isolated endophytic fungi was identified as Neopestalotiopsis sp. and Peniophora lycii using molecular analysis method. The antibacterial activity was carried out by using microdillution method. The antibacterial properties from mycelium extracts showed moderate to low antibacterial activity with Minimum Inhibitory Consentration (MIC) values of 125-500 Âµg mL-1 against Eshcerichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923 bacteria. The n-hexane extract of both endophytic fungi shows the strongest antibacterial activity against Escherichia coli with MIC values of 125 Âµg mL-1